2019
DOI: 10.1021/acs.jpcc.9b05117
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Geometric Effects on Chemical Reactivity of 3d-Transition-Metal-Doped Silver Cluster Cations toward Oxygen Molecules

Abstract: We report electronic and geometric structures of 3d-transition-metal-doped silver cluster cations, Ag N−1 M + (M = Sc−Ni), studied by chemical reaction with oxygen molecules. The evaluated reaction rate coefficients for small sizes, N, are 2− 6 orders of magnitude higher than those of undoped Ag N + , whereas those for large N are comparable with those of Ag N + .The low reactivity at large sizes is attributed to a geometric effect, that is, encapsulation of the dopant atom, which provides an active site locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
(57 reference statements)
4
15
0
Order By: Relevance
“…Finally, the overall reaction rate coefficient was evaluated for each size of Ag n + to show size dependence of the reactivity; the extinction rate constants of the reactant clusters were divided by the number density of NO in the ion trap under the assumption that the elementary reaction is first order for NO. Reaction rate coefficients thus obtained are plotted in Figure , along with reaction rate coefficients against O 2 that were previously measured . Note that the reactivities of Ag 3 + and Ag 5 + are so low that no product ion was observed in the present measurement, which is also the case for Ag 5 + , Ag 7 + , and Ag 9 + reacting with O 2 .…”
Section: Results and Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Finally, the overall reaction rate coefficient was evaluated for each size of Ag n + to show size dependence of the reactivity; the extinction rate constants of the reactant clusters were divided by the number density of NO in the ion trap under the assumption that the elementary reaction is first order for NO. Reaction rate coefficients thus obtained are plotted in Figure , along with reaction rate coefficients against O 2 that were previously measured . Note that the reactivities of Ag 3 + and Ag 5 + are so low that no product ion was observed in the present measurement, which is also the case for Ag 5 + , Ag 7 + , and Ag 9 + reacting with O 2 .…”
Section: Results and Discussionsupporting
confidence: 61%
“…Reaction rate coefficients thus obtained are plotted in Figure 5, along with reaction rate coefficients against O 2 that were previously measured. 67 Note that the reactivities of Ag 3 + and Ag 5 + are so low that no product ion was observed in the present measurement, which is also the case for Ag 5 + , Ag 7 + , and Ag 9 + reacting with O 2 . In general, the reactivity toward NO was found to be about 3 orders of magnitude higher, except for n = 3 and 5, than that toward O 2 .…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…Time-dependent measurements were performed to evaluate the depletion rate constant of the reactants, Ag n Ce + and Ag n Sm + , which was divided by the oxygen concentration to obtain a reaction rate coefficient in the same way as reported for 3d-transition-metal-doped clusters . The reaction rate coefficients thus obtained for Ag n Ce + and Ag n Sm + are shown in Figure a,b, respectively, along with those of undoped Ag n + .…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we have reported systematic measurements of reactivity of the doped clusters against O 2 ; oxygen etching is frequently employed to examine the stability of the clusters. When multiple-collision reaction experiments are performed, not only the reactivity but also successive elementary reaction processes can be elucidated. We have found that the doped anionic clusters, Ag 14 Sc – , Ag 13 Ti – , and Ag 12 V – , as well as cationic clusters, Ag 16 Sc + , Ag 15 Ti + , Ag 14 V + , Ag 11 Fe + , Ag 10 Co + , and Ag 9 Ni + , exhibit a reactivity minimum in the size-dependent measurement of reaction rate coefficients along with reaction kinetics; the low reactivity suggests that these clusters are stable due to the 18-electron shell closure including delocalized 3d electrons of the dopant atom. In contrast, Ag 9 Fe – , Ag 8 Co – , and Ag 7 Ni – , possessing an exohedral dopant geometry, were highly reactive even with 18 valence electrons, which suggests that an endohedral geometry plays a key role in 3d delocalization …”
Section: Introductionmentioning
confidence: 99%